Financing the 2008 Election : Assessing Reform - Corrado, Anthony, 1957-; Magleby, David B. (Book collections on Project MUSE., 2011)
"Provides analysis of how campaign finance and spending shaped the historic presidential and congressional races of 2008; latest in a series of volumes on the costs and trends of campaign finance published since 1960"--Provided by publisher.